Analisis Pendapatan dalam Menentukan Kelayakan Usahatani Buah Naga di Desa Tottong Kecamatan Donri-Donri Kabupaten Soppeng - Desi Oktavia; Mustari Mustari; Marhawati Marhawati; Tuti Supatmaningsih; Nurdiana Nurdiana (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
Abstract. This study aims to determine whether dragon fruit farming in Tottong Village, Donri-Donri Distrct, Soppeng Regency is feasible to be cultivated. This research is a quantitative descriptive study using income analysis, R/C ratio analysis and Break even Point analysis. The number of respondents in this study were 60 people. The result showed that the income of dragon fruit farmers in Tottong Village Donri-Donri Distrct, Soppeng Regency experienced profits and was feasible to cultivate. With an average income of IDR 985,993.000 per 88 are land area. And the R/C value is 1,1 Keywords: Income Analysis, Tottong Village, R / C Ratio, Break Even Point